Characterization of Strontium Ferrite Based on Natural Iron Sand at Banjar Beach with Co and Zn Ion Doping as Generator Material Electricity - Rahmat, Solihin; Jaswadi; Istiqomah; Asyil Arifah; Melani Aulia Khatami; Susilawati; Ziadatul Fatimah; Esa Imaniah; Dedi Riyan Rizaldi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This research aims to determine the characteristics of strontium-based on ferrite natural iron sand doped with Co and Zn ions as an electric generator driver. Iron sand contains minerals such as magnetite (Fe3O4), hematite (α-Fe2O4), and maghemite (γ-Fe2O3) which can be used to making permanent magnets. The method used is coprecipitation to produce nano-sized magnetite minerals which are used as a basic material in permanent magnets production. In order to increase the magnetic and electrical properties, Co and Zn doping is added with several concentrations (x = 0.0; 0.5; 1.0). The final result is a sample powder that has been heated at a temperature of 80 ˚C for 24 hours. More higher the calcination temperature used, made more darker result sample color. The FT-IR test results show the presence of O-H, Sr-O, Co-O, Zn-O, and Fe-O compounds at certain wavelengths ranging from 400-690 cm-1.